Pemodelan Evaluasi Konsumsi Energi Komputer pada Tahap Pengembangan Perangkat Lunak - Fauzie Nursandah; Bambang Subiyanto; Arthur Daniel Limantara; Hery Lilik Sudarmanto; Sri Wiwoho Mudjanarko (CAHAYAtech, 2021)
A